Controlled Self‐assembly of Nanographdiynes Mediated by Molecular Dipoles Induced by Rotatory Asymmetric Substituents - Chen, Jing; He, Jingyi; Wu, Xingzhong; Li, Yongjun (Chemistry : a European journal, 2025)
The discrete π‐ stacks of specific lengths and orientation is crucial for understanding the impact of intermolecular interactions on optical or electronic properties of nanographdiynes. We designed and synthesized nanographdiynes modified with bulky rotatable asymmetric substituents. The peripheral substituents with different push‐pull electronic properties can induce molecular dipoles perpendicular to nanoGDY π surface with different orientation. Mediated by directional dipole‐dipole interactions, o‐TBGDY substituted with electron‐donating tert‐butylphenyl groups cofacially dimerized with a twist angle, involving intermolecular interlocking of ortho‐substituted tert‐butylphenyl groups. In contrast, OTFGDY substituted with electron‐withdrawing trifluorophenyl groups formed dimeric H‐aggregates with an in‐plane shift along one diyne linkage, in which the ortho‐substituted trifluorophenyl groups point toward the outside of the interacting π‐plane. o‐TBGDY can only exist as isolated H‐dimer in the solid state, while OTFGDY can form a hybrid tetramer of H‐ and J‐aggregates. Our researches reveal a new method for preparing discrete π‐stacked dye assemblies with well‐defined optoelectronic properties. Rotatory bulky asymmetry substituents were introduced at the edge of nanographdiynes to induce molecular dipole. And directional dipole‐dipole interactions guided these nanographdiynes, which were substituted by groups with different push‐pull electronic properties, to self‐assemble into different π‐π stacked H‐dimers. These dimers exhibited different conformations, different abilities to further aggregation, and ultimately had different optical properties.